PENINGKATAN MOTIVASI BELAJAR DAN PEMAHAMAN SISWA MELALUI PEMBELAJARAN GEOMETRI BERBANTUAN PROGRAM KOMPUTER “WINGEOM” PADA POKOK BAHASAN BANGUN DATAR - Novi Mayasari (LPPM Press STKIP PGRI Pacitan, 2016)
This research is a classroom action research (CAR) conducted in order to determine whether (a) increase student motivation in learning geometry (Flat) that uses a computer program medium